Evaluation of Gelling Behavior of Natural Gums and their Formulation Prospects - Mohan, Rachit; Singh, Shobha; Kumar, Geetendra; Srivastava, Manjoosha (Indian Journal of Pharmaceutical Education and Research, 2020)
Purpose: Gums and polymers can be found abundantly in the nature from various plants, microbial and marine sources. Their physical and functional characteristics can be customized according to its application in product development. The purpose of this study is to determine the potentiality of natural gums obtained from plant based sources in development of gel formulation and its comparison with the commercially used polymers viz. Carbapol 934, Carboxy Methyl Cellulose, Xanthan, Sodium Alginate. Methods: Gel formulations of varying ranges of polymeric concentrations were prepared and evaluated for its pharmaceutical parameters like pH, viscosity, homogeneity, tensile strength and antimicrobial activity. Results: The analysis of the developed gel formulations indicated that formulations developed using Guar gum possess much better gelling behavior i.e. viscosity and muco-adhesiveness then other selected gums and is more closer to its synthetic counterpart like Carbopol 934. Thus natural gum provides a comparatively broader range of characteristics and eco-friendly approach which enhances its applicability in formulation development. This research work rationalizes the importance of natural gums as gelling agents in development of pharmaceutical dosage forms, cosmetic products and nutraceutical formulations.
Keywords: Eco-friendly; Gelling agents; Gel Formulations; Muco-adhesiveness; Antimicrobial activity